POLA KONSUMSI PANGAN, AKTIVITAS FISIK, RIWAYAT PENYAKIT, RIWAYAT DEMENSIA KELUARGA, DAN KEJADIAN DEMENSIA PADA LANSIA DI PANTI WERDHA TRESNA BOGOR - Chairunnisa Utami Pratiwi; Sri Anna Marliyati; Melly Latifah (Food and Nutrition Society of Indonesia, 2013)
The objective of this study were to analyze the patterns of food consumption, physical activity, history of disease, family history of dementia, and incidence of dementia in elderly in Werdha Tresna, nursing home, Bogor. Research design was cross sectional study with 42 elderly as subjects. The results showed that there were significant correlation between the level of education, adequacy of level vitamin A, vitamin B1, vitamin B2, vitamin B6, vitamin C, history of diabetes and physical activity with incidence of dementia in elderly (p<0.05). There were no significant correlation between age, adequacy of level folic acid, history of hypertension, and family history of dementia with incidence of dementia in elderly (p>0.05).